The influence of genre on adolescent discourse skills: Do narratives tell the whole story? - Hill, Lizz; Whitworth, Anne; Boyes, Mark; Ziegelaar, Monique; Claessen, Mary (TAYLOR & FRANCIS LTD, 2021)
Purpose: Narrative is the dominant focus of traditional standardised discourse assessment, yet the complex discourse needs of adolescence has led to increased interest in profiling skills in other monologic genres for this age group. This interest is not commensurate with a robust understanding of the influence of genre on adolescent discourse across word to whole-text language features. This knowledge is important to inform context(s) for assessment to profile strengths and weaknesses in discourse-level language. Method: One hundred and sixty adolescents between 12 and 15 years (M= 13;1, SD= 1;1, 55% female, 45% male) completed the Curtin University Discourse Protocol–Adolescent. Samples of recount, narrative, expository and persuasive discourse were coded using a multi-level analysis procedure. Result: Genre had a significant influence on language variables regardless of age. Narrative tasks citied the longest, most lexically diverse, cohesive, coherent and well-structured output. Results were consistent with the oral to literate continuum and the order in which genres are introduced in the academic curriculum. Conclusion: Structure, content and domain-specific knowledge likely influenced the genre-related differences seen in this study. It would be advantageous to sample a range of monologic genres when assessing adolescent discourse. Declarative knowledge may be an important consideration in topic selection.